The Diagnostic Performance of DCE-MRI in Evaluating the Pathological Response to Neoadjuvant Chemotherapy in Breast Cancer: A Meta-Analysis - Cheng, Qingqing; Huang, Jiaxi; Liang, Jianye; Ma, Mengjie; Ye, Kunlin; Shi, Changzheng; Luo, Liangping (Frontiers in Oncology, 2020)
Background: Neoadjuvant chemotherapy (NAC) is commonly utilized in preoperative treatment for local breast cancer, and it gives high clinical response rates and can result in pathologic complete response (pCR) in 6%–25% of patients. In recent years, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been increasingly used to assess the pathological response of breast cancer to NAC. In present analysis, we assess the diagnostic performance of DCE-MRI in evaluating the pathological response of breast cancer to NAC. Materials and Methods: A systematic search in PubMed, the Cochrane Library, and Web of Science for original studies was performed. The Quality Assessment of Diagnostic Accuracy Studies-2 tool was used to assess the methodological quality of the included studies. Patient, study, and imaging characteristics were extracted, and sufficient data to reconstruct 2 × 2 tables were obtained. Data pooling, heterogeneity testing, forest plot construction, meta-regression analysis and sensitivity analysis were performed using Stata version 12.0 (StataCorp LP, College Station, TX). Results: Eighteen studies (969 patients with breast cancer) were included in the present meta-analysis. The pooled sensitivity and specificity of DCE-MRI were 0.80 (95% confidence interval [CI]: 0.70, 0.88) and 0.84 (95% [CI]: 0.79, 0.88), respectively. Meta-regression analysis found no significant factors affecting heterogeneity. Sensitivity analysis showed that studies that set pathological complete response (pCR) (n=14) as a responder showed a tendency for higher sensitivity compared with those that set pCR and near pCR together (n = 5) as a responder (0.83 vs 0.72), and studies (n=14) that used DCE-MRI to early predict the pathological response of breast cancer had a higher sensitivity (0.83 vs 0.71) and equivalent specificity (0.80 vs 0.86) compared to studies (n=5) that assessed the response after NAC completion. Conclusion: Our results indicated that DCE-MRI had good diagnostic performance and can be considered an important auxiliary method to evaluate the pathological response of breast cancer to NAC. In addition, setting pCR as a pathological responder may improve the diagnostic sensitivity of DCE-MRI. DCE-MRI also had good diagnostic performance in predicting the pathological response of breast cancer to NAC.